Erratum: XIN LI, XIULAN HE, WEIXIONG SHI, SHUYU ZUO, XUE LI, DI PENG, ZHAOHUI GUO & LEI SU (2025) Penicillium sinense, a new species of endophytic fungi from Citrus trifoliata with inhibition activities to pathogenic fungi. Phytotaxa 720 (3): 224–236. - Li, Xin; He, Xiulan; Shi, Weixiong; Zuo, Shuyu; Li, Xue; Peng, Di; Guo, Zhaohui; Su, Lei (Phytotaxa, 2025)
N/A